Necrotizing interstitial pneumonia and suppurative myocarditis associated with Bartonella henselae infection in three Florida pumas. (September 2018) - Elsmo, Elizabeth J.; Fenton, Heather; Cleveland, Christopher A.; Shock, Barbara; Cunningham, Mark; Howerth, Elizabeth W.; Yabsley, Michael J.
Three Florida pumas ( Puma concolor coryi ) that had spent time in captivity prior to being released in the wild were found exhibiting respiratory signs and reluctance to move. All 3 pumas died shortly after immobilization, despite supportive veterinary care. Significant autopsy findings included necrotizing interstitial pneumonia, with pulmonary edema and hyaline membranes, and suppurative myocarditis. Organisms morphologically consistent with Bartonella henselae were identified in intravascular histiocytes in the lung of one of the pumas on histopathology and confirmed via transmission electron microscopy. B. henselae was detected in fresh lung tissue and confirmed by PCR and sequence analysis (16S-23S spacer region, pap31, and rpoB genes) from one of the affected pumas. In all affected pumas, B. henselae was detected by PCR in formalin-fixed, paraffin-embedded lung tissue, and positively staining organisms were identified in sections of lung by immunohistochemistry for B. henselae. In situ hybridization detected B. henselae DNA in lung tissue from 2 of 3 affected pumas. Our case series suggests that B. henselae can be associated with a fatal disease syndrome in Florida pumas. The cause of susceptibility to fatal disease associated with B. henselae infection in these pumas remains unknown.